Consumo de álcool e tabaco entre idosos na atenção primaria à saúde em uma unidade básica no Brasil - Figueroa Oviedo, Paulo César [UNIFESP] (2019)
Objective: To estimate the prevalence of alcohol and tobacco consumption among older people in primary care in Brazil, and identify the factors associated with this consumption before and after the age of 65. Methods: Secondary analysis of a cross-sectional study of 87 older people representing all people over 65 registered in a primary care unit (n=541). Alcohol and tobacco consumption was identified through self-report and confirmed by an informant. Fourteen units per week was used as the cut-off to identify at risk drinking before the age of 65 and seven units per week after this age. For moderate alcohol consumption, consumption of 1-6 units/weeks after 65 years (current consumption) and 1-13 units/weeks for the period before 65 years of age. For tobacco, information was obtained regarding the typical amount consumed (cigarettes per day) and for how long (in years), age at regular onset, and age at which smoking stopped. Weighted logistic regression was used to identify potential sociodemographic characteristics associated with alcohol and tobacco consumption. Results: 51.3% of the sample were women, almost half of the sample (43.2%) were 75 years of age or older. Fourteen participants were current drinkers (16.1%), and 6 of them (6.9%) were at risk drinkers. Only one current drinker started drinking after the age of 65. Thirty-two participants (34%) had drunk before the age of 65, and among them 11(15.8%) were assessed as having been at risk drinkers. Of these 11 drinkers who had past risk consumption, 2 (18.2%) had become moderate drinkers after the age of 65; 3 (27.3%) continued to be at risk drinkers and six (54.5%) had stopped drinking. Multivariate analysis was adjusted for sociodemographic characteristics. Only male gender was associated with past (OR= 3.83 95% CI 1,24- 11,88) and although not statistically significant there was a predominance of current alcohol consumption in men also. Regarding tobacco consumption, 6 (6.8%) participants reported current consumption and 27 (31.3%) reported being smokers before the age of 65. As per alcohol consumption, only male gender was associated with past consumption (before 65 years ago) (OR= 5.30 95% CI 1,65- 17,03). Due to the sample size and small number of current smokers it was not possible to run the adjusted analyses for current consumption. Conclusion: The prevalence of alcohol consumption among people over 65 is relatively high and it seems to start at a younger age and extends to this age group, with a small proportion of older people who have started drinking after 65 years. Male gender should be the target of interventions to reduce alcohol consumption at this age group. The elderly are more susceptible to the effects of alcohol and tobacco due to their greater physical fragility and the presence of comorbidities and polypharmacy. There is an urgent need for a better understanding of drinking behaviors among older people so that prevention and treatment strategies are better defined for that specific population. Larger and more robust studies are need to better understand this behavior among older Brazilians and the real need of interventions directed to this behavior among older people in primary care.